TEACHERS’ STRATEGIES IN INCREASING STUDENTS’ ENGLISH LEARNING MOTIVATION DURING THE ERA OF NEW NORMAL - Devi Juniartati; Citra Kusumaningsih; Elly Syahadati (Journal of English Language Teaching and Education (JELTE), 2023)
This research aims to determine teacher strategies in increasing students' English learning motivation during the era of the new normal and find out whether the strategies applied by teachers can increase students' English learning motivation during the era of the new normal at SMP Negeri 4 Sajingan Besar for the academic year of 2021/2022. This research is in the form of a qualitative descriptive. The data collection technique is a combination of direct and indirect methods. The participants of this research were 2 English teachers and 15 students. Data was collected using interviews, questionnaires, and documentation. The results showed that the teacher used several strategies to increase students' English learning motivation during the era of the new normal and found out whether the strategies applied by the teacher could increase students' learning motivation during the era of new normal, the teacher used demonstration, small group discussion, blended learning, and games. The most increasing motivation with the strategy used is extrinsic motivation.